The Relationship between Compliance with Medication and Blood Pressure in Hypertension Sufferers - Sujatmiko (KHD Production, 2024)
Hypertension is a chronic medical condition that requires long-term management through medication and lifestyle changes. Adherence to the treatment regimen is a key factor in controlling blood pressure and preventing potentially fatal complications. This study aims to evaluate the relationship between adherence to medication consumption and blood pressure in hypertension sufferers. This study used a cross-sectional design involving 40 respondents who were diagnosed with hypertension at several health centers in Nganjuk City. Data was collected through a questionnaire that measured the patient's level of compliance with taking antihypertensive drugs and blood pressure checks carried out by medical personnel. The results of the analysis showed that there was a significant relationship between the level of adherence to taking medication and the level of blood pressure control (p < 0.05). Patients who have a high level of compliance tend to have better controlled blood pressure compared to patients who are not compliant. These findings emphasize the importance of improving adherence to treatment in hypertension management to achieve optimal health outcomes.